2011
DOI: 10.1002/adfm.201102361
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Functionalized Silicate Nanoparticles as a Fenton‐Type Catalyst for Water Purification by Advanced Oxidation Processes (AOP)

Abstract: Wet hydrogen peroxide catalytic oxidation (WHPCO) is one of the most important industrially applicable advanced oxidation processes (AOPs) for the decomposition of organic pollutants in water. It is demonstrated that manganese functionalized silicate nanoparticles with interparticle porosity act as a superior Fenton‐type nanocatalyst in WHPCO as they can decompose 80% of a test organic compound in 30 minutes at neutral pH and room temperature. By using X‐ray absorption spectroscopic techniques it is also shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(79 citation statements)
references
References 34 publications
2
72
0
1
Order By: Relevance
“…10 Therefore, heterogeneous Fenton processes (Fig. S1b, ESI †) are developed to address these problems: 11,12 however, few of them exhibit significant catalytic efficiency at neutral pH values in water, and they typically use a large excess of H 2 O 2 (above the stoichiometric amount by 100-fold) to reach a desirable efficiency of these materials. 13 17,18 or the aromatic products of the pollutants, 16,19 adding UV irradiation, 20 and establishing a precious metal Fenton system to utilize phenol.…”
Section: Introductionmentioning
confidence: 99%
“…10 Therefore, heterogeneous Fenton processes (Fig. S1b, ESI †) are developed to address these problems: 11,12 however, few of them exhibit significant catalytic efficiency at neutral pH values in water, and they typically use a large excess of H 2 O 2 (above the stoichiometric amount by 100-fold) to reach a desirable efficiency of these materials. 13 17,18 or the aromatic products of the pollutants, 16,19 adding UV irradiation, 20 and establishing a precious metal Fenton system to utilize phenol.…”
Section: Introductionmentioning
confidence: 99%
“…Tušar vd. 2012'te yayımladıkları çalışmada mangan içeren silikat nanopartikül Fenton benzeri katalizörleri ile 50 ppm metilen mavisi çözeltisini arıtmak için 0,4 g/L katalizör kullanmışlardır [15].…”
Section: Katalizör Yüklemesi Etkisi (Effect Of the Catalyst Loading)unclassified
“…Due to their strong toxicity even at low concentration [3], development of efficient treatment technologies is in urgent demand. Advanced oxidation processes (AOPs) involving Fenton reaction, photocatalysis, electrocatalysis and various chemical methods have attracted intensive research interests for decomposing the organic contaminants due to their high efficiency and complete degradation capability [4]. Previous investigations have demonstrated that Fenton/Fenton-like reactions utilizing hydroxyl radicals (OH·) could decompose organic contaminants efficiently [5,6].…”
Section: Introductionmentioning
confidence: 99%